Evolución De La Desigualdad Y Pobreza En Nicaragua En El Periodo De 1991 A 2014 - Carlos Ernesto Luquez Gaitán; Ernest Yasser Núñez Betancourt; Manuel del Valle Sánchez (European Scientific Journal, ESJ, 2018)
This paper discusses the situation of the evolution of inequality and poverty from a historical perspective, including the structural reforms in Nicaragua during the decade of 1990. It also examines the decline in poverty in Nicaragua from 1991 through World Bank indicators. Methods of measuring inequality and poverty such as the Gini coefficient, GDP per capita, and the incidence rate of poverty, as well as the poverty gap, are used. It includes the results of quantitative assessment of poverty and inequality, and concludes with a decline in poverty. There is evidence of a steady increase in real GDP and a steady trend in the unemployment rate.